PENGEMBANGAN MEDIA PEMBELAJARAN MENGGUNAKAN ADOBE FLASH UNTUK MENINGKATKAN HASIL BELAJAR PKn - Rahmaibu, Farid Ahmadi, Fitria Dwi Prasetyaningsih, Farida Hasan (Jurnal Kreatif : Jurnal Kependidikan Dasar, 2016)
This research was aim to developed, feasibility, and compare differences in learning out-comes before and after used Adobe Flash based multimedia on Civic Education instructi-onal of globalization content at 4B grade Al Madina Islamic Elementary School of District Semarang. This type was the Research and Development involve Waterfall model, they were analysis, design, implementation, and testing. Eligibility was based on the evaluation of media experts and small scale trials. Collected data through interviews, documentation, questionnaire, and test. Analysis techniques were including analysis of product data, norma-lity test, and then analysis N-gain and paired samples t-test. The percentage obtained from subject matter experts was 90% (a very decent used). The percentage achieved by expert media was 80%, (fit for use). Results of researched small scale trials has improved with the acquisition of comprehension in the middle criteria. Questionnaire responses of students stating that if the media in very well and the questionnaire responses of teachers in both criteria. Evidenced on the results of the average post-test sample class, that is 83, compared to the average pre-test is only 71.75. N-gain result was in middle criteria. The conclusions of this study is the instructional media Flash feasible and effective used and to improved student learning outcomes of Civic Education.Keywords: Adobe Flash; Civic; development; media